2009
DOI: 10.1111/j.1651-2227.2009.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced basal salivary cortisol in children with asthma and allergic rhinitis

Abstract: Asthmatic children on moderate or high doses of inhaled corticosteroids had reduced salivary cortisol, but co-morbidity of asthma and rhinitis was also associated with reduced cortisol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 28 publications
3
36
2
1
Order By: Relevance
“…Some researchers have also detected lower cortisol levels among patients with inflammatory diseases [13][14][15]17].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have also detected lower cortisol levels among patients with inflammatory diseases [13][14][15]17].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a chemical in saliva depends on its chemical characteristics; both lipophilic and nonionized molecules pass from blood to saliva better than hydrophilic and ionized molecules (Esteban and Castaño 2009). Saliva is most frequently used for the diagnosis of hereditary disorders, autoimmune diseases, malignant and infectious diseases, and endocrine disorders, as well as in the assessment of therapeutic levels of drugs and the monitoring of illicit drug use (Kaufman and Lamster 2002;Bakkeheim et al 2010). Although saliva is not currently used for environmental exposure, recently, children from primary schools provided saliva samples for a cotinine assay to evaluate changes in children's exposure to second-hand smoke after the implementation of smoke-free legislation (Holliday et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Children with established allergic disease differ in cortisol response to stress and have altered basal cortisol levels compared with healthy children. 16,17 We have previously shown that school children of families with an anthroposophic lifestyle seem to have a lower prevalence of allergic diseases [18][19][20] and recently that infants in these families have low levels of salivary cortisol and of allergic sensitization. 21,22 The aim of this study was to investigate whether salivary cortisol levels early in life are associated with the development of allergic sensitization and symptoms during early childhood.…”
mentioning
confidence: 98%